2023
DOI: 10.2174/1573405619666230216114748
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Theragnostics in Breast Cancer: A Systematic Review of the Last 12 Years

Abstract: Background: Breast cancer is the most common malignancy in women, with high morbidity and mortality. Molecular alterations in breast cancer involve the expression or upregulation of various molecular targets that can be used for diagnostic nuclear medicine imaging and radiopharmaceutical treatment. Theragnostics is based on the binding of radionuclides to molecular targets. These radionuclides can induce a cytotoxic effect on the specific tumor cell (target) or its vicinity, thus allowing a personalized approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 155 publications
0
1
0
Order By: Relevance
“…Leitner et al also found that greater tumor glucose uptake is generally observed in patients with BC with increased BMI compared to patients with normal BMI [ 18 ]. Increased uptake of [ 18 F]F-FDG is generally associated with a worse outcome for patients, particularly in those with grade 3 tumors compared to those with grade 1 or 2 tumors [ 19 ]; nevertheless, the combined influence of being overweight may be even more detrimental for prognosis [ 4 , 14 ]. Indeed, a study explored the link between visceral adipose tissue (VAT) metabolic activity, assessed via preoperative [ 18 F]FDG PET/CT scans, and axillary lymph node (ALN) metastasis in 173 postmenopausal luminal breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Leitner et al also found that greater tumor glucose uptake is generally observed in patients with BC with increased BMI compared to patients with normal BMI [ 18 ]. Increased uptake of [ 18 F]F-FDG is generally associated with a worse outcome for patients, particularly in those with grade 3 tumors compared to those with grade 1 or 2 tumors [ 19 ]; nevertheless, the combined influence of being overweight may be even more detrimental for prognosis [ 4 , 14 ]. Indeed, a study explored the link between visceral adipose tissue (VAT) metabolic activity, assessed via preoperative [ 18 F]FDG PET/CT scans, and axillary lymph node (ALN) metastasis in 173 postmenopausal luminal breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%